The reproductive health understanding: an analysis for the prevention of children sexual harassment - Sukmawati, Indah; Engku Kamarudin, Engku Mardiah; Afdal, Afdal; Fikri, Miftahul; Zikra, Zikra; Iswari, Mega; Hariko, Rezki (International Journal of Public Health Science (IJPHS), 2024)
Understanding reproductive health is an important issue for students with special needs as their specificity does not prevent the acquisition and comprehension including efforts to prevent sexual harassment. Descriptive cross-sectional design was used. The samples selected were 86 students in Indonesia which were 29 males and 57 females, consisting of 36% deaf (n=31), 50% mentally retarded (n=43), and 13.9% autistic (n=12). Data were collected with a questionnaire of 34 items which measured the understanding of reproductive processes, functions, and systems, as well as sexually transmitted diseases, attitudes about reproductive health, media and social influence on sexual activity and ability to communicate. The data were analyzed descriptively and different multivariate tests were carried out based on the type of student's impairment. Consequently, their understanding of reproductive health was discovered to be low, especially in terms of sexually transmitted diseases (STDs), attitudes, and communication skills. The results also showed that there was no significant difference in the understanding of reproductive health in students with special needs concerning the type of disability suffered. These can be used by teachers, counselors, and the subjects plus their parents as initial information on developing an understanding of reproductive health in the future.